(3ETcGdjGJ GdJfejI GdGbJUGOjI GdeJhGRfI (B:s (3OQGSI ebGQfI (B/s - (3ONjd, eMeO MSfs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2009)
(3OQGSI GTcGdjGJ HMKjI GSGSjI jJYdb GHQRgG HGdJGKjQ GdeJHGOd Hjf GdJfejI hGdSjGSI MjK Hjf GdYdGbI Hjf GdJfejI hGdOjehbQGWjI hGgejI GdJfejI aj GdehGKjb GdOhdjI h GdGbdjejI h GdTQGFY GdOjfjI h aj eQJcRGJ GdfXGe GdSjGSj eY hVY eKGd Mj Ydi GdhGbY GdGfeGFj aj dHfGf(B.s
(3eQGLY U(B.417 (3; edGMb U(B.377s
Keywords: (3GdGbJUGOs; (3GdJfejIs; (3GdJfejI GdGbJUGOjIs